2018
DOI: 10.1080/15402002.2018.1483368
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sleep loss and risk-taking behavior: Does the origin of sleep loss matter?

Abstract: Whether sleep loss is associated with risk-taking behavior or not could depend on the origin of sleep loss and the underlying personality traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…Several studies suggested an increase in physicians' risk‐taking behaviour after acute sleep deprivation 59,60 . However, studies investigating risk taking in other settings failed to reach a consistent conclusion 61,62 …”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested an increase in physicians' risk‐taking behaviour after acute sleep deprivation 59,60 . However, studies investigating risk taking in other settings failed to reach a consistent conclusion 61,62 …”
Section: Discussionmentioning
confidence: 99%
“…In sum, video game playing could have negative consequences in term of sleep quality and health. However Rusnac et al (2018) reported sleep deprivation could also produce or enhance risk-taking and sensation seeking (e.g., in video game playing). In turn, poor sleep quality could maintain and increase video game playing and affect mental health.…”
Section: Discussionmentioning
confidence: 99%
“…The association between higher risk propensity and sleep/wake pattern disruption reported by O'brien and Mindell [65] may support the assumption according to which risk-takers are more used to sleep deprivation and therefore able to tolerate it better compared to risk-avoiders. Moreover, a study from Rusnac et al [66] demonstrated that chronic sleep deprivation is associated with increased RTB and higher scores on a sensationseeking scale only in subjects who voluntary reduce sleep duration compared to subjects who reduce it involuntarily, i.e. suffering from insomnia.…”
Section: Discussionmentioning
confidence: 99%